Associations of traditional cardiovascular risk factors with 15-year blood pressure change and trajectories in Chinese adults: a prospective cohort study - Zhang, Y; Sun, Q; Yu, C; Sun, D; Pang, Y; Pei, P; Du, H; Yang, L; Chen, Y; Yang, X; Chen, X; Chen, J; et al. (Lippincott, Williams & Wilkins, 2024)
Objective: How traditional cardiovascular disease (CVD) risk factors are related to long-term blood pressure change (BPC) or trajectories remain unclear. We aimed to examine the independent associations of these factors with 15-year BPC and trajectories in Chinese adults.